Seroprevalence of Brucella Infection among Students at Amran University- Yemen - Al-Hadheq, Ali Ahmed; Al-Mahbashi, Anas; Al-Wajeeh, Talal; Al-Haj, Asia; Edrees, Wadhah Hassan (Journal of Amran University, 2024)
Background and Aim: Brucella infection in animals is considered a great problem in most countries around the world and is considered one of the important pathogenic zoonosis infections in humans. This study aimed to determine the prevalence of Brucella infection among students at Amran University, Yemen. Methods: It is a cross-sectional study carried out among 247 students between January 2023 and November 2023. Blood samples were collected and Brucella Antigen was detected using immunochromatographic technology. Results: Out of 247 human samples 17 samples (6.9%) were positive for brucella Antigen 2 (1.75%) were positive among males, and 15 (12.5%) were positive among females. Regarding the residence of students the results showed that 49 (19.8%) were from Amran City and 198 (80.2%) from rural areas, The risk factors for Brucella infection were ranching, drinking milk without pasteurization, and direct contact with livestock. Conclusion: The prevalence of brucellosis was low among the study's participants but it will become a serious problem that threatens the health care system in Yemen. So, awareness programs should be provided to students and the general population about Brucella infection and its risk factors